The Mediation of Economic Literacy on the Effect of Self Control on Impulsive Buying Behaviour Moderated by Peers - Efendi, Riyanto; Indartono, Setyabudi; Sukidjo, Sukidjo (International Journal of Economics and Financial Issues, 2019)
Impulsive buying is a trait that tends to be found in every individual, especially in the era of industrial revolution 4.0. The term impulsive purchase is a person’s behavior in shopping in a spontaneous, reflective, sudden and automatic manner without knowing the item is needed or not for himself. The purpose of this study was to determine the effect of self-control on impulsive purchases mediated by economic literacy and moderated by peers. The methodology of this research is quantitative research involving respondents as many as 191 students taken by proportional random sampling technique. Data multiple linear regression by using SPSS Version 20 is used to analyze the data. The research results show that; (1) Self-control gives a negative and significant influence on impulsive buying, (2) Economic literacy mediate the influence of the relationship of self-control to impulsive buying, and (3) Peers moderate the mediation of economic literacy of self-control on impulsive buying. Keywords: Economic Literacy, Self-Control, Impulsive Buying, Peers JEL Classifications: M21, M31, M38, M51 DOI: https://doi.org/10.32479/ijefi.7738